A method for mutagenesis of mouse mtDNA and a resource of mouse mtDNA mutations for modeling human pathological conditions. Issue 9 (27th March 2015) - Fayzulin, Rafik Z.; Perez, Michael; Kozhukhar, Natalia; Spadafora, Domenico; Wilson, Glenn L.; Alexeyev, Mikhail F.
Abstract: Mutations in human mitochondrial DNA (mtDNA) can cause mitochondrial disease and have been associated with neurodegenerative disorders, cancer, diabetes and aging. Yet our progress toward delineating the precise contributions of mtDNA mutations to these conditions is impeded by the limited availability of faithful transmitochondrial animal models. Here, we report a method for the isolation of mutations in mouse mtDNA and its implementation for the generation of a collection of over 150 cell lines suitable for the production of transmitochondrial mice. This method is based on the limited mutagenesis of mtDNA by proofreading-deficient DNA-polymerase γ followed by segregation of the resulting highly heteroplasmic mtDNA population by means of intracellular cloning. Among generated cell lines, we identify nine which carry mutations affecting the same amino acid or nucleotide positions as in human disease, including a mutation in the ND4 gene responsible for 70% of Leber Hereditary Optic Neuropathies (LHON). Similar to their human counterparts, cybrids carrying the homoplasmic mouse LHON mutation demonstrated reduced respiration, reduced ATP content and elevated production of mitochondrial reactive oxygen species (ROS). The generated resource of mouse mtDNA mutants will be useful both in modeling human mitochondrial disease and in understanding the mechanisms of ROS production mediated by mutations in mtDNA.